2009
DOI: 10.1002/chem.200901257
|View full text |Cite
|
Sign up to set email alerts
|

Single and Consecutive Cyclization Reactions of Alkynyl Carbene Complexes and 8‐Azaheptafulvenes: Direct Access to Polycyclic Pyrrole and Indole Derivatives

Abstract: The reactivity of alkynyl and enynyl Fischer carbene complexes towards 8-azaheptafulvenes is examined. Alkynyl carbenes 1 a-f undergo regioselective [8+2] heterocyclization with 8-aryl-8-azaheptafulvenes 2 a, b providing cycloheptapyrroles 3 and 4 with metal carbene or ester functionality at C3. Moreover, consecutive cyclization reactions are involved when enynyl carbenes are used. Thus, the cyclopenta[b]pyrrole framework 7 is formed by the consecutive [8+2] cyclization and cyclopentannulation reactions. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…Fischer methoxy cyclopropylethynyl chromium carbene complex, [37] alkynylcyclopropanecarboxylic esters, [10,12] alkynylcyclopropanecarboxylic acids 1, [12] alkynylcyclopropanecarboxamides 2a-c, [12] and alcohol 3 a [12] have been previously synthesized and were prepared as described. All reactions involving air sensitive compounds were carried out under inert atmosphere (Ar or N 2 , !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fischer methoxy cyclopropylethynyl chromium carbene complex, [37] alkynylcyclopropanecarboxylic esters, [10,12] alkynylcyclopropanecarboxylic acids 1, [12] alkynylcyclopropanecarboxamides 2a-c, [12] and alcohol 3 a [12] have been previously synthesized and were prepared as described. All reactions involving air sensitive compounds were carried out under inert atmosphere (Ar or N 2 , !…”
Section: Methodsmentioning
confidence: 99%
“…IPrAuCl and AgOTs were purchased from commercial supplies and lyophilized prior to use. Fischer methoxy cyclopropylethynyl chromium carbene complex, alkynylcyclopropanecarboxylic esters, [10, 12] alkynylcyclopropanecarboxylic acids 1 , alkynylcyclopropanecarboxamides 2a – c , and alcohol 3 a have been previously synthesized and were prepared as described. Azepinones 5a – c and bicyclic enol ethers 7 a and 8 a have been previously reported by us, and dihydropyranones 17 a,d have also been described .…”
Section: Methodsmentioning
confidence: 99%
“…Then, 1,2-dichloroethane was confirmed as the most effective mediumf or this reaction after as olvents creening; thus, under the same reactionc onditions, the conversion and yield were significantly lower for non-polar solvents such as toluene, hexane, or more polar solvents such as THF or acetonitrile (Table 1, entries 4-7). Then, the evaluation of other gold catalysts confirmed that the change of the ligand resulted ineffective to improve the transformation (Table 1, entries 8, 9). Furthermore, the use of gold (III) complex did not improve the results achieved with the phosphite ligand (Table 1, entry 10).…”
Section: Resultsmentioning
confidence: 98%
“…[6] The first studies on this transformation involved the use of electron-deficient unsaturated systems as 2p partners; for instance, double-activateds tyrenes [7] and cumulenes [8] (Figure 1a). Later, it was described that the highly-electrophilic alkenyl [5a] and alkynyl [9] Fisher carbene metal complexes can react as 2p component with high efficiency and selectivity (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of chromium or tungsten carbene complexes, similar yields are observed. According to a tentative mechanism, 190 is obtained by an initial Michael addition of fulvene to a carbene complex (Scheme 33B), and heterocycle 187 by the subsequent cyclization [153] …”
Section: Fischer Carbene Complexes With Metal‐mediated Higher‐order Cycloadditionsmentioning
confidence: 99%